Success story Rehabilitasi Ekosistem Mangrove di Pantai Karangsong Kabupaten Indramayu - Oni Oni; Cecep Kusmana; Sambas Basuni (Graduate School Bogor Agricultural University (SPs IPB), 2019)
The success of Kelompok Pantai Lestari (KPL) to rehabilitate the mangrove ecosystem at Karangsong is the result of innovation in the nursery aspect at the planting site, using multiplanting planting techniques, installation of wave breaker, maintenance with fertilization and spraying, clear and clean (legal and conflict free) of land status, village level that binds all stakeholders. Management of rehabilitated mangrove ecosystem management at Karangsong beach implemented collaborative management (government, private and non-profit organizations), The analysis of the local institutional sustainability of KPL as managers of CPRs of mangrove ecosystems based on eight principles of sustainability of CPRs shows strong results of sustainability on two principles namely the boundaries of the CPRs resource area (4.36) and recognize of the right to organize and manage resources (4.13). Sustainability category one principles that have the lowest value is the principle of applying sanctions to local rules / village regulations (2.47). The average value of the eight principles of local KPL institutional sustainability managing the CPRs of the mangrove ecosystem at Karangsong is 3.54 which is included in the strong sustainability category. Management of rehabilitated mangrove ecosystem resources in Karangsong by KPL should be supported by issuing local regulations on mangrove ecosystem management in Indramayu Regency to improve the governance and ecosystem benefits of sustainable mangrove for ecological, economic and socio-cultural aspects.